Intrapulp peroxide concentration of teeth submitted to violet LED-assisted in-office bleaching - Perches, Carolina; Gobbo, Vanessa Cavalli; Kury, Matheus; Tabchoury, Cínthia Machado Pereira; Giannini, Marcelo (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2018)
The aim of this study was to investigate the intrapulp penetration of peroxide due to in-office bleaching light-activated with a novel violet LED light. Forty bovine incisors were selected and bleaching was performed on enamel surface in a delimited area, as follows (n=10): (LED/HP) 35% hydrogen peroxide bleaching associated with 20 violet LED irradiations of 1-min and 30-s intervals, (HP) 35% hydrogen peroxide bleaching, (LED/CP) 37% carbamide peroxide bleaching associated with violet LED irradiations and (CP) 37% carbamide peroxide bleaching. Bleaching was applied on enamel for 30-min in three appointments with 7-day intervals. In the last session, acetate buffer was placed in the pulp chamber during the gel application and afterwards, transferred to a test-tube with horseradish peroxidase and leucocristal violet. The intrapulp concentration of HP was evaluated by means of spectrophotometry. Data were analyzed by one-way ANOVA and Tukey’s test. Differences were observed in the intrapulp concentration of HP for the LED/HP and LED/CP groups (p=0.025). However, the intrapulp concentration of HP did not increase with the violet LED irradiation (p>0.05). In conclusion, violet LED-irradiation did not influence the intrapulp peroxide concentration, but the HP concentration was dependent on the bleaching gel concentration.